HUBUNGAN INISIASI MENYUSUI DINI ( IMD) TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH PUSKESMAS MUMBULSARI KABUPATEN JEMBER: The Relationship of Early Breastfeeding Initiation (EBI) and Exclusive Breastfeeding In The Mumbulsari Public Health Center, Jember Regency, 2022 - Dinar Perbawati (LPPM - STIKES Pemkab Jombang, 2022)
Early Breastfeeding Initiation (EBI) is one of the government's policies to reduce the neonatal mortality rate (NMR) and increase the coverage of exclusive breastfeeding. One of the efforts to prevent infant mortality is to provide exclusive breastfeeding for infants in an effective and efficient manner. Low Early Breastfeeding Initiation (EBI) is one of the factors related to the failure of exclusive breastfeeding. The purpose of this study was to analyze the relationship between Early Breastfeeding Initiation (EBI) and exclusive breastfeeding at the Mumbulsari Public Health Center, Jember Regency. The purpose of this study was to analyze the relationship between Early Breastfeeding Initiation (EBI) and exclusive breastfeeding at the Mumbulsari Public Health Center, Jember Regency. This research was conducted in May 2022. The population in this study were 114 mothers with toddlers who were in the Mumbulsari Public Health Center, Jember Regency in 2022, the number of samples was 35 people. This type of research is analytic by using a cross sectional design. Research data collection by taking primary and secondary data, analyzed with chi-square statistical test. The results of the statistical test showed that the value of p = 0.001 showed that Ha was accepted and H0 was rejected, meaning that there was a relationship between the IMD variable and exclusive breastfeeding at the Mumbulsari Public Health Center, Jember Regency (p <0.05). The result of the correlation coefficient value is 0.519, which means the level of closeness of the relationship is in the medium category.